5' upstream sequences from the wun1 gene are responsible for gene activation by wounding in transgenic plants. - Logemann, J (1989)
A 1.2-kilobase pair fragment of the 5' upstream region of a potato wound-inducible gene (wun1) was fused to different marker genes (wun1-CAT, wun1-NPTII). Stable integration of a wun1-CAT chimeric gene into the tobacco genome led to a high wound-inducible chloramphenicol acetyltransferase activity in leaves. Transient expression experiments in potato protoplasts showed that wun1 carries a strong promoter sequence similar in strength to the 35S promoter. The same intensity of expression was also observed using wun1 constructs in transient experiments with rice protoplasts. wun1 mRNA was shown to accumulate to high levels in potato leaves collapsing as a result of infection with the phytopathogen Phytophthora infestans. The wun1 product might, therefore, play a role in a general physiological reaction to stress correlated with cell death.